Implementing the Halalan Tayyiban food quality management framework: some considerations for the actors - Md Dahlal, Norazilawati; Mohamed Saniff, Shereeza (Human Resource Management Academic Research Society (HRMARS), 2019)
The development of the halal food industry today is based on the Halalan Tayyiban food quality management (HTFQM) framework. The HTFQM framework is universally adopted based on the product’s superior quality in hygiene, safety and purity. The external characteristics of the product are more emphasized than its internal characteristics. This is a critical issue that can inhibit the effectiveness of HTFQM framework. Thus its impact has exposed a gap. This paper identifies the gap and discusses the important elements in the HTFQM framework. This paper uses a sequential qualitative multimethod approach combining two data collection methods to explain the needed features to build the ideal dimension of the elements. The study is divided into two phases. The study was conducted by obtaining primary data through face-to-face interviews and thereafter content analysis of the HTFQM framework. It is discovered that the HTFQM framework has not applied all the elements contained in the halalan tayyiban concept. The evaluation of the HTFQM framework accentuates the physical and technical aspects. The paper presents the analysis which proves that an ideal HTFQM framework can be formed provided the aspects of the physical, and material, the spiritual and supernatural aspects are included too with practical suggestions.